Surfactant Therapy in Meconium Aspiration Syndrome: A Case Report - Dyatmika Tanaya, Putu Wahyu; Ida Ayu Sri Kusuma Dewi; Nyoman Ananda Putri Prashanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Meconium aspiration syndrome (MAS) is one of many causes of respiratory distress in newborns. Data regarding MAS in Indonesia is still very limited, but a study revealed MAS is related to a high mortality rate. The latest study revealed surfactant therapy is related to better clinical outcomes in MAS cases. This study aimed to present a case of a baby with meconium aspiration syndrome given bolus surfactant therapy. Case presentation: A day-old baby was referred to our emergency department with respiratory distress, delivered by cito caesarean section due to cephalopelvic disproportion with premature rupture of membranes. The baby didn’t cry immediately; bluish skin and green amniotic fluid were found. The baby was already intubated from the referring hospital, and the physical examination revealed rales on both lungs with severe work of breath. Chest radiography revealed patchy opacities in the right lung hemisphere, suggesting MAS. Echocardiography revealed a small patent ductus arteriosus, and head ultrasonography revealed mild brain oedema. The baby received bolus bovine surfactant therapy at 16 hours of age, delivered through an endotracheal tube. Clinical improvement was observed, and supplementary oxygen was reduced gradually. The baby was able to maintain good oxygenation without supplemental oxygen by day 12th and was able to breastfeed and drink from the bottle. He was discharged with good condition. Conclusion: Surfactant therapy can become a safe and effective treatment modality in MAS. Further study is still needed regarding time, method, and types of surfactants used in MAS management.